An Analysis of Customer Awareness and Perception towards Life Insurance in Hyderabad (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Insurance companies play a vital role in promoting human well-being by offering protection to millions against life risks such as unforeseen death or accidents. Life insurance, in particular, has emerged as one of the fastest-growing sectors in India following privatization and increased foreign direct investment (FDI). Consequently, understanding customer perception and awareness regarding life insurance products and companies has become increasingly important. This study, based on primary data, involved collecting responses through a questionnaire from 500 policyholders in Hyderabad. The data was analyzed using statistical tools such as percentages, means, and frequencies.